2016
DOI: 10.1007/s00704-016-1874-y
|View full text |Cite
|
Sign up to set email alerts
|

Future projections of synoptic weather types over the Arabian Peninsula during the twenty-first century using an ensemble of CMIP5 models

Abstract: CitationEl Kenawy AM, McCabe MF (2016) Future projections of synoptic weather types over the Arabian Peninsula during the twenty-first century using an ensemble of CMIP5 models. Theor Appl Climatol. response, but may also be used to inform impact studies pertinent to water resource planning 29 and management, extreme weather analysis and agricultural production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Bador et al 91 , 92 (2018, 2020) and Pfahl et al 93 presented a widespread intensification of total and extreme precipitation in the mid-to-high latitudes of the Northern Hemisphere that has been influenced by the thermodynamic response of the increasing surface temperatures. The contribution of the precipitation extremes supports the projected increase in the annual precipitation total for the study region 94 98 .…”
Section: Resultssupporting
confidence: 67%
“…Bador et al 91 , 92 (2018, 2020) and Pfahl et al 93 presented a widespread intensification of total and extreme precipitation in the mid-to-high latitudes of the Northern Hemisphere that has been influenced by the thermodynamic response of the increasing surface temperatures. The contribution of the precipitation extremes supports the projected increase in the annual precipitation total for the study region 94 98 .…”
Section: Resultssupporting
confidence: 67%
“…Southwest Asia is expected to experience the highest rate of population growth among major areas in the coming decades (Roudi‐Fahimi and Kent, ), and this might lead to a decrease in water availability by almost 40% by 2050 (Terink et al, ). Moreover, many studies revealed that climate change will significantly affect temperature and precipitation patterns in Southwest Asia (e.g., Black, ; Evans, ; Lelieveld et al, ; Terink et al, ; Hijioka et al, ; Almazroui et al, ; El Kenawy and McCabe, ). For example, Evans () has studied future temperature and precipitation conditions over the Middle East, using an ensemble of 18 GCMs, and indicated that the temperature would increase from 1.4 to 4°C by the end of this century under the A2 emissions scenario.…”
Section: Introductionmentioning
confidence: 99%
“…Pérez et al (2014) showed the different performance for reproducing synoptic patterns in a larger set of GCMs as part of the Coupled Model Intercomparison Project phase 3 (CMIP3, Meehl et al 2007) and phase 5 (CMIP5, Taylor et al 2012), respectively. El Kenawy and McCabe (2016) assessed the capability of a set of CMIP5 models to reproduce synoptic conditions over the Arabian Peninsula, and they suggested that models with higher spatial resolution tend to perform better than those models with coarser resolution. In this context, several authors suggest that the model performance for reproducing circulation types might dependent on the study region as well as the selected variable, and they show that some models give more realistic results, but there is no single one GCM better than others (Belleflamme et al 2013;Casado and Pastor 2012).…”
Section: Introductionmentioning
confidence: 99%